Assessing translation quality: a survey of research into human translation, post-editing and machine translation - D’Angelo, Francesca (Annali del Dipartimento di Studi Letterari, Linguistici e Comparati. Sezione linguistica, 2024)
The article investigates the relationship between human translation, post-editing and machine translation addressing, in particular, the controversial issue of translation quality. An overview of different methodologies and approaches is provided, identifying a number of perceived issues concerning translation in terms of process, product, and evaluation systems. A discussion on the observed tendency to objectify translation standards, and to automatic metrics, is included with a focus on the implications it may have for the research and translation community.